Cannabinoquinones: Synthesis and Biological Profile - Caprioglio, Diego (Biomolecules, 2021)
Neutral cannabinoids are oxidatively unstable and are converted into quinone derivatives by atmospheric- and/or chemical oxidative dearomatization. The study of cannabinoquinones has long been plagued by their lability toward additional oxidative degradation, but full substitution of the quinone ring, as well as the introduction of steric hindrance on the alkyl substituent, have provided sufficient stability for a systematic investigation of their bioactivity and for further clinical development. These studies culminated in the discovery of the aminocannabinoquinone VCE-004.8 (5), a compound under phase 2 clinical development with orphan drug status by EMA and FDA for the management of scleroderma. The synthesis and rich chemistry of these compounds will be described, summarizing their biological profile and clinical potential.